The Combined Effect of Electrical Stimulation and High-Load Isometric Contraction on Protein Degradation Pathways in Muscle Atrophy Induced by Hindlimb Unloading. (5th October 2011) - Fujita, Naoto; Murakami, Shinichiro; Fujino, Hidemi
Abstract : High-load isometric exercise is considered an effective countermeasure against muscle atrophy, but therapeutic electrical stimulation for muscle atrophy is often performed without loading. In the present study, we investigated the combined effectiveness of electrical stimulation and high-load isometric contraction in preventing muscle atrophy induced by hindlimb unloading. Electrical stimulation without loading resulted in slight attenuation of muscle atrophy. Moreover, combining electrical stimulation with high-load isometric contraction enhanced this effect. In electrical stimulation without loading, inhibition of the overexpression of calpain 1, calpain 2, and MuRF-1 mRNA was confirmed. On the other hand, in electrical stimulation with high-load isometric contraction, inhibition of the overexpression of cathepsin L and atrogin-1 mRNA in addition to calpain 1, calpain 2, and MuRF-1 mRNA was confirmed. These findings suggest that the combination of electrical stimulation and high-load isometric contraction is effective as a countermeasure against muscle atrophy.